2014
DOI: 10.4028/www.scientific.net/msf.794-796.155
|View full text |Cite
|
Sign up to set email alerts
|

Grain Refinement Efficiency of a New Oxide-Containing Master Alloy for Aluminium Casting Alloys

Abstract: In this study, grain refinement efficiency of a new oxide-containing master alloy was demonstrated on an A357 alloy. The grain size of the reference alloy was reduced by 50-60% with the addition of the master alloy and introduction of ultrasonic cavitation. A higher addition of master alloy was found to be not benificial in further reducing the grain size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The grain size was reduced for reference alloys from 900 µm (Fig 4 The initial grain size was noticed to be ~900 µm. The grain size was reduced appreciably with the addition of master alloys [15]. However, there was no more grain size reduction observed above 1.7 wt.% of MA addition.…”
Section: Almentioning
confidence: 85%
“…The grain size was reduced for reference alloys from 900 µm (Fig 4 The initial grain size was noticed to be ~900 µm. The grain size was reduced appreciably with the addition of master alloys [15]. However, there was no more grain size reduction observed above 1.7 wt.% of MA addition.…”
Section: Almentioning
confidence: 85%
“…Recent work showed that ultrasonication was capable of dispersion of in situ MgAl 2 O 4 particulates in liquid metal, while manual or mechanical stirring apparently failed to distribute fine particles in the liquid metal. [14,21] The presence of free Ti in the master alloy adds to the grain-refining effect through growth restriction. This becomes evident if one compares the results reported on the grain refinement by a similar master alloy with spinel but without Ti [14] (Figure 16) with the results reported in this article.…”
Section: Mechanisms Of Grain Refinementmentioning
confidence: 99%
“…[14,21] The presence of free Ti in the master alloy adds to the grain-refining effect through growth restriction. This becomes evident if one compares the results reported on the grain refinement by a similar master alloy with spinel but without Ti [14] (Figure 16) with the results reported in this article. For the reader's convenience, the data are summarized in Figure 17.…”
Section: Mechanisms Of Grain Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…G is the shear modulus, E m is the young modulus of matrix alloy, 68 GPa, is the Poisson's ratio, 0.33, b is the Burger's vector (0.286nm), is the dislocation density induced by CTE mismatch, which can be calculated by the equation [35] …”
Section: Coefficient Of Thermal Expansion (Cte) Mismatch Strengtheningmentioning
confidence: 99%